Detection of X-Ray Doses with Color-Changing Hackmanites: Mechanism and Application - Vuori Sami; Colinet Pauline; Norrbo Isabella; Steininger Ralph; Saarinen Timo; Palonen Heikki; Paturi Petriina; Rodrigues Lucas CV; Göttlicher Jörg; Le Bahers Tangui; Lastusaari Mika (WILEY-V C H VERLAG GMBH, 2022)
Hackmanites, a variety of sodalite with the general formula Na8Al6Si6O24(Cl,S)(2), are a family of nature-based smart materials having the ability for reversible photochromism upon UV or X-ray exposure. Being nontoxic, cheap, and durable, hackmanite would be an optimal material for the visual detection of the presence of X-rays in simple portable systems. However, its X-ray-induced coloring abilities are so far known only qualitatively. In this work, a combination of experimental and computational methods is used to reveal the mechanism of X-ray-induced color changing in these materials. Finally, their use is demonstrated both in color intensity-based X-ray dosimetry and photochromic X-ray imaging.